Statistical Analysis of Balanced Brain and IQ Applications - Mahfuzah, Mustafa; M. Nasir, Taib; Zunairah, Murat; Sahrim, Lias; Norizam, Sulaiman (2013)
EEG signal research had been studied massively in such balanced brain and IQ applications. This paper focuses on correlation between balanced brain and Intelligence Quotient (IQ) applications. At first, the raw EEG signals from both applications need to pre-process to remove artefact and unwanted frequency. Then, the EEG signals will go through statistical processes which are Scatterplot and Correlation test. As a result, there is correlation between the balanced brain and IQ application with strong and significant Pearson correlation.